REVITALISASI KAWASAN KOTA TUA CIREBON - Bobby Halim; Dwi Susilastuti; Anita Armas (Besaung : Jurnal Seni Desain dan Budaya, 2017)
This study focuses at the old town of Cirebon. This study assessed through three disciplines, namely visual communication design, architecture and product design. The layout of the old town of Cirebon is located in Yos Sudarso. This study through the stages of observation, literature review and interviews. This study is also a qualitative one. Special study of the visual communication design, using Semiotics. Not easy to draw conclusions from three authors (researchers) let alone different background knowledge. Hopefully, through this research, local authorities may consider the Cirebon city and realize the conclusions and solutions that have been done by the author. Key words: revitalitaion, semiotics, city, branding